Α‐trideuteromethyl[15N]glutamine: A long‐lived hyperpolarized perfusion marker. Issue 6 (29th January 2016) - Durst, Markus; Chiavazza, Enrico; Haase, Axel; Aime, Silvio; Schwaiger, Markus; Schulte, Rolf F.
Abstract : Purpose: We characterized the performance of a novel hyperpolarized perfusion marker, α‐trideuteromethyl[15N]glutamine, for direct comparison with a 13C‐based hyperpolarized perfusion marker, [13C, 15N2]urea. Methods: A hardware platform and pulse sequence for in vivo 15N experiments were established. Hyperpolarized solutions of α‐trideuteromethyl[15N]glutamine and [13C, 15N2]urea were injected into healthy male Lewis rats. Kidney slice images were acquired using a single‐shot spiral readout. Both compounds were compared to determine in vivo signal lifetime and tracer distribution. Mass spectrometry was performed to evaluate excretion of the compound. Results: Compared with 13C‐labeled urea, a significantly increased signal lifetime was observed. While the urea signal was gone after 90 s, decay of the glutamine compound was sufficiently slow to obtain a quantifiable signal, even after 5 min. The glutamine derivative showed strong localization in the kidneys with little background signal. Effective T1 of α‐trideuteromethyl[15N]glutamine was approximately eight‐fold higher than that of urea. Mass spectrometry results confirmed rapid excretion within the time scale of the measurement. Conclusion: Hyperpolarized α‐trideuteromethyl[15N]glutamine is a highly promising candidate for renal studies because of its long signal lifetime, strong localization and rapid excretion. Magn Reson Med 76:1900–1904, 2016. © 2016 International Society for Magnetic Resonance in Medicine